الصفات التميزية لفصل الصفصاف الشائعSalix acmophylla Boiss.عن الصفصاف الابيضS. alba L.في محافظة دهوك - شهباز, سليم اسماعيل (Sulaimani Journal for Pure and Applied Sciences, 2002)
Salix acmophylla Boiss. and S.alba L. are common trees or shrubs on mountain valleys and water resources in Duhok governorate . both exhibit close morphological similarities . We realized that characters as leaf blade margins, stipules , shape and size of catkin -scales (Bracts ),anthers, as well as the cuticular structure and anatomical features of leaf blade cross section had not been sufficiently and effectively utilized for distinguishing the two closely related taxa . The data obtained from various investigations proved that size and or shape of stipules , catkin- scales , anthers , stomata , normal epidermal cells and number of stomata / mm2 are of mach taxonomic significance to discriminate both of the species . Many anatomical characteristics are common in both species . stomata are amphestomatic the pattern of subsidiary cells arrangement is Brachyparacytic Two palisade layers are found towards the adaxial leaf surface , with commonly 4 and rarely 3 or 5 spongy layers towards the abaxial leaf surface .
Keywords: Cuticulaar Struicuture; Stomata; Salik acmophylla Salba